Three Concepts for Spatial Development of Irkutsk - Kozmin, Alexei (project baikal, 2016)
It is crucial for a present-day big city not to reduce the process of spatial planning to elaboration of a formal master plan and other town-planning documents. The spatial planning should flow from the city development strategy and be based on real economic projects and demographic potential. At the same time, strategic planning should include a spatial component, because implementation scenarios for strategic plans come from the condition of the territory, possibilities and limitations of urban space.
Keywords: Irkutsk city master plan; planning framework; landscape potential; public spaces